Genetic diversity of Phytophthora infes tans isolates collected in potato fields of Costa Rica using RAPDs - Páez, Oswaldo (2005)
In order to determine the genetic diversity of Phytophthora infestans in Costa Rica, a total of 62 isolates were collected in potato-growing regions of Cartago, Zarcero, Heredia and Fraijanes during 1999-2001 and subjected to a RAPD analysis. All isolates were previously assayed for mating type and meta laxyl resistance. By using 11 primers, it was possible to generate 17 RAPD genotypes, with frequencies ranging from 0.55 to 0.02. Resistant and susceptible isolates coming from all sampled zones were found in the most frequent group. All isolates from the 17 groups showed a genetic relationship. The highest genetic variation was found among isolates; therefore, the population structure was not fractioned as a result of the production zone or the sensitivity to metalaxyl. Analyses with the Gst coefficient showed no genetic similarities between Costa Rican and the foreign (US-1, US-18, and EC-1) isolates. In conclusion, RAPD analysis revealed the genetic diversity of the P. infestans population in Costa Rican potato fields, although there is a possibility that all isolates are sharing a common ancestor.